2020
DOI: 10.1002/brb3.1546
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide exposure during late embryogenesis triggers and drives Alzheimer‐like behavioral and neuropathological changes in CD‐1 mice

Abstract: Introduction Infections could contribute to Alzheimer's disease (AD) neuropathology in human. However, experimental evidence for a causal relationship between infections during the prenatal phase and the onset of AD is lacking. Methods CD‐1 mothers were intraperitoneally received lipopolysaccharide (LPS) with two doses (25 and 50 μg/kg) or normal saline every day during gestational days 15–17. A battery of behavioral tasks was used to assess the species‐typical behavior, sensorimotor capacity, anxiety, locomot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 55 publications
3
15
0
Order By: Relevance
“…This result was consistent with those of previous studies that indicated that age-related decline in cognitive impairment begins at 12–13 months of age in this strain mouse ( Wang H. et al, 2010 ; Wang et al, 2020 ). Several studies have suggested that embryonic inflammation and adolescent stress can accelerate brain age-associate cognitive impairment ( Li X. W. et al, 2016 ; Bhagya et al, 2017 ; Wang et al, 2020 ). In contrast, an adolescent EE can relieve the deficits in hippocampal synaptic plasticity, memory, and anxiety caused by chronic stress ( Bhagya et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result was consistent with those of previous studies that indicated that age-related decline in cognitive impairment begins at 12–13 months of age in this strain mouse ( Wang H. et al, 2010 ; Wang et al, 2020 ). Several studies have suggested that embryonic inflammation and adolescent stress can accelerate brain age-associate cognitive impairment ( Li X. W. et al, 2016 ; Bhagya et al, 2017 ; Wang et al, 2020 ). In contrast, an adolescent EE can relieve the deficits in hippocampal synaptic plasticity, memory, and anxiety caused by chronic stress ( Bhagya et al, 2017 ).…”
Section: Discussionsupporting
confidence: 93%
“…Our results showed that spatial learning and memory were impaired in the middle-aged mice. This result was consistent with those of previous studies that indicated that age-related decline in cognitive impairment begins at 12-13 months of age in this strain mouse Wang et al, 2020). Several studies have suggested that embryonic inflammation and adolescent stress can accelerate brain age-associate cognitive impairment Bhagya et al, 2017;Wang et al, 2020).…”
Section: The Effects Of Embryonic Inflammation and Adolescent Psychossupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, repeated systemic LPS injections even lead to a prolonged elevation of Ab levels and cognitive deficits (38)(39)(40). Strikingly, pregnant mice exposed to repeated systemic LPS causes AD-related features including behavioral and neuropathological changes in their offspring (41).…”
Section: Evidence From Preclinical Studiesmentioning
confidence: 99%
“…Although the mouse strain CD1 has been widely used to examine multiple aspects of the general aging process [15][16][17], its alveolar morphometric analysis has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%